2013
DOI: 10.1002/jat.2962
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the toxicity of food additive silica nanoparticles on gastrointestinal cells

Abstract: Silica nanoparticles (NPs) have been widely used in food products as an additive; however, their toxicity and safety to the human body and the environment still remain unclear. As a food additive, silica NPs firstly enter the human gastrointestinal tract along with food, thus their gastrointestinal toxicity deserves thorough study. Herein, we evaluated the toxicity of food additive silica NPs to cells originating from the gastrointestinal tract. Four silica NP samples were introduced to human gastric epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 47 publications
3
41
0
Order By: Relevance
“…37,39 Scientists have evaluated the toxicity of SiO 2 NP as a food additive on gastrointestinal cells, indicating their safety as food additive, but suggested the necessity of long-term in vivo studies to confirm their safety profile. 40 Recently, researchers have reported that interactions between food additive SiO 2 NPs and food matrices were highly dependent on the type of food component. 41 Moreover, the experimenters have suggested that toxicity of SiO 2 NPs depends on size, dose, and cell type.…”
Section: Nanomaterials In Daily Life and Their Toxicitymentioning
confidence: 99%
“…37,39 Scientists have evaluated the toxicity of SiO 2 NP as a food additive on gastrointestinal cells, indicating their safety as food additive, but suggested the necessity of long-term in vivo studies to confirm their safety profile. 40 Recently, researchers have reported that interactions between food additive SiO 2 NPs and food matrices were highly dependent on the type of food component. 41 Moreover, the experimenters have suggested that toxicity of SiO 2 NPs depends on size, dose, and cell type.…”
Section: Nanomaterials In Daily Life and Their Toxicitymentioning
confidence: 99%
“…CeO 2 , a rare-earth lanthanide element oxide, is mainly used in slurries for silicon wafer planarization [12], as automotive fuel additives to improve the efficiency of combustion [34], and as automobile catalytic converters [5]. SiO 2 nanoparticles are employed in the fabrication of electric and thermal insulators [6], as drug-delivery systems in nanomedicine [78], as anticaking and thickener agents in food production [910], as well as in cosmetics, drugs and printer toners [11]. …”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of amorphous silica nanoparticles has been assessed both at the cellular level and in animal models. For example, on the basis of the results of a study using human gastric epithelial GES-1 cells and colorectal adenocarcinoma Caco-2 cells, Yang et al suggested that silica nanoparticles (200-450 nm) may arrest the cell cycle and inhibit cell growth but they do not induce apoptosis or necrosis 54) . We previously demonstrated that silicon was not detected in the liver or blood of mice after a 28-day daily oral exposure at a total dose of about 3.5 g silica particles/kg body weight, and that none of the particles tested showed toxic biological effects 36) .…”
Section: Applications and Safety Of Silica Nanoparticles Used In The mentioning
confidence: 99%